Pengaruh Struktur Corporate Governance terhadap Integritas Laporan Keuangan Perusahaan pada Perusahaan LQ45 yang Terdaftar di BEI - Inosensius Istiantoro; Ardi Paminto; Herry Ramadhani (Faculty of Economics and Business Mulawarman University, 2017)
The influence of Corporate Governance Structure on Integrity Corporate Financial Statements of the LQ45 companies listed on the Indonesia Stock Exchange 2009-2014. (Under the guidance of Dr. H. Ardi Paminto, MS and Herry Ramadhani, SE., MM). The purpose of research is to analyze the influence of Corporate Governance Structure on Integrity Corporate Financial Statements of the LQ45 companies listed on the Indonesia Stock Exchange 2009-2014. The data used in this study is 18 companies using criteria through purposive sampling method. Analysis of the data used in this study is the classical assumption test and multiple linear regression SPSS 19.0. The results of this study indicate that the institutional ownership has a negative and significant influence on integrity corporate financial statements, Managerial Ownership is positive but no significant effect on integrity corporate financial statements, Audit Committee is positive and has a significane effect on integrity corporate financial statements, Independent Commissioner is negative and no significant effect on integrity corporate financial statements.Keywords: Institutional Ownership, Managerial Ownership, Audit Committee and Independent Commissioner.